2017
DOI: 10.26443/el.v24i1.150
|View full text |Cite
|
Sign up to set email alerts
|

The Prison Library: A Vital Link to Education, Rehabilitation, and Recreation

Abstract: This article has been adapted from a paper presented by the author in Cienfuegos, Cuba, November 1999 at the invitation ofUNEAC (U nion Nacional de Escritores y Aristas Cubano) and the provincial public library in Cienfuegos.In cooperation with other prison programs the prison library plays a critical part in the education and rehabilitation of incarcerated persons. The background, roles, services, and ways in which the modern prison library can meet the needs of both inmates and prison staff are examined in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…The information needs of Australian prisoners have not been examined in the literature; however, some international studies have explored this question. Lehmann (2000) identified that in America, prisoners have much the same needs for information as the general public, but have a reduced capacity to satisfy those needs due to the lack of free access to resources, such as public libraries. Greenway (2007) identifies information about current affairs and parenting as important to American prisoners.…”
Section: Education and Information Needs Of Australian Prisonersmentioning
confidence: 99%
See 2 more Smart Citations
“…The information needs of Australian prisoners have not been examined in the literature; however, some international studies have explored this question. Lehmann (2000) identified that in America, prisoners have much the same needs for information as the general public, but have a reduced capacity to satisfy those needs due to the lack of free access to resources, such as public libraries. Greenway (2007) identifies information about current affairs and parenting as important to American prisoners.…”
Section: Education and Information Needs Of Australian Prisonersmentioning
confidence: 99%
“…She writes specifically about Polish prison libraries and identifies various programs in which they play a role, such as rehabilitation and re-integration programs, culture and art programs, and the general promotion of reading to raise literacy levels, and facilitate knowledge attainment. Lehmann (2000) identifies prison libraries in the United States as being integral to the education programs in prisons. Her examples indicate that prison education staff can integrate library materials into their curriculum and that the presence of a library can enable independent study by prisoners.…”
Section: The Role Of Prison Libraries In Prisoner Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Key factors contributing to reoffending include lack of social support, homelessness, and unemployment (Graham, 2016;Healy, 2010;Shapland et al 2016), with educational deficits long considered a significant underpinning factor (e.g. Nuttal et al 1998;Lehmann, 1999;Ministry of Justice, 2010). Rehabilitation programmes, beyond tertiary and/or vocational educational goals, aim to effect meaningful psychological and behavioural change in prisoners to reduce the likelihood of reoffending (Ministry of Justice, 2010); and encourage self-reflection and acquisition of new knowledge via non-confrontational approaches to correcting problematic attitudes or behaviours (Raynor and Robinson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, according to Campbell (2000), information needs can be defined as the perception of a lack of information that provokes one to then develop a need for it. Prisoners are regarded as disadvantaged people because they lack free access to many things in a free society, including libraries (Lehmann, 2000). The value of the prison library cannot be underestimated (Bowe, 2011).…”
Section: Introductionmentioning
confidence: 99%